Soluble TREM‐1, as a new ligand for the membrane receptor Robo2, promotes hepatic stellate cells activation and liver fibrosis. Issue 24 (9th November 2021) - Liu, Ting; Chen, Shujia; Xie, Xiaoli; Liu, Hongqun; Wang, Yongjuan; Qi, Shengbin; Shi, Linping; Zhou, Xue; Zhang, Jiuna; Wang, Shuling; Wang, Yijun; Chen, Shengxiong; et al.
Abstract: Triggering receptor expressed on myeloid cells‐1 (TREM‐1) exists in two forms: a transmembrane form and a soluble form (sTREM‐1). The levels of sTREM‐1 are elevated in supernatants of activated HSCs. However, the role of sTREM‐1 in HSC activation and liver fibrosis remains undefined. Previous studies have primarily focused on the transmembrane form of TREM‐1; we innovatively observed the function of sTREM‐1 as a ligand in liver fibrosis and screened its receptor. Here, recombinant sTREM‐1 was used as a stimulator which induced HSC activation and further aggravated liver fibrosis. Then, screening for sTREM‐1 interacting membrane receptors was performed using pull‐down assay followed by mass spectrometry, and the membrane receptor roundabout guidance receptor 2 (Robo2) was identified as a candidate receptor for sTREM‐1. The interaction between sTREM‐1 and Robo2 was verified by pull‐down and immunofluorescence. The role of Robo2 on sTREM‐1‐induced HSC activation and its downstream signal pathways was assessed by knockdown of Robo2 in LX‐2 cells. Furthermore, HSC‐specific knockdown of Robo2 was achieved in a mouse model of liver fibrosis by using a recombinant adeno‐associated virus (AAV) vector to confirm the role of the receptor, and we proved that Robo2 knockdown inhibited the activation of HSC and liver fibrosis, which also led to the inactivation of Smad2/3 and PI3K/Akt pathways in sTREM‐1‐induced HSC activation and liver fibrosis. In conclusion, sTREM‐1 acts as a new ligand of Robo2; the binding of sTREM‐1 to Robo2 initiates the activation of the downstream Smad2/3 and PI3K/Akt signalling pathways, thereby promoting HSC activation and liver fibrosis.